Voting behaviour in the 19th German Bundestag and beyond: between the aily business of unity and a special vote of conscience - Mai, Philipp; Link, Moritz; Engler, Fabian (German politics, 2024)
The literature on the voting behaviour of members of parliament (MPs) has two prominent strands: the study of dissenting voting behaviour in whipped votes and of voting behaviour in votes of conscience. This article examines both aspects for the 19th German Bundestag (2017-2021). First, we assess the determinants of dissenting voting behaviour in all whipped votes in this term and compare them to the three previous terms of Angela Merkel’s chancellorship. Logistic multi-level regressions show that mostly political factors account for lower (offices, electoral security) or higher (parliamentary experience, GDR socialisation) defection rates. Second, we assess the determinants of voting behaviour on the organ donation reform in 2020. Theoretically, we identify a value conflict between self-determination and collective health interests that substantially differs from earlier free votes. Logistic regression analyses reflect this conflict: Besides individual religious denomination and union or party membership, it is especially constituency characteristics such as the share of Catholics that affect voting behaviour. Consequently, voting on free votes is affected by both political and personal characteristics of the MP. Overall, we show that MPs are exposed to various and, depending on what the vote is on, different influences that have to be reconciled.
Gesehen am 07.03.2024